Bismuth-doped 3D carbon felt/PbO2 electrocatalyst for degradation of diuron herbicide and improvement of pesticide wastewater biodegradability. Issue 1 (February 2023) - Rahmani, Alireza; Ansari, Amin; Seid-mohammadi, Abdolmotaleb; Leili, Mostafa; Nematollahi, Davood; Shabanloo, Amir
Abstract: A bismuth-doped three-dimensional networked carbon felt/PbO2 (CF/Bi-PbO2 ) anode was developed for the electrocatalytic degradation of diuron and treatment of real pesticide wastewater. The prepared PbO2 anodes were characterized by FESEM, XRD, EDX, BET-BJH, accelerated lifetime test, LSV, CV and EIS. Bi doping in the PbO2 matrix significantly increased the electrochemical active area (3.17 vs. 1.57 m 2 g −1 ), oxygen evolution potential (2.3 vs. 1.95 V) and service time (143 vs. 76 h) of CF/Bi-PbO2 anode compared to pristine CF/PbO2 . The results showed that the optimized degradation efficiency of diuron by CF/Bi-PbO2 anode at pH 5 and a current density of 15 mA cm −2 after 25 min of reaction is 97.6 %. However, it took 50 min to remove COD with 98.7 % efficiency. The possible pathways of electrocatalytic degradation of diuron were discussed using HPLC-mass data. The electrocatalytic performance of PbO2 anodes was compared under optimal conditions for real pesticide wastewater treatment. Accordingly, the kinetic constant of COD removal by Bi-doped anode (0.0101 min −1 ) was about 2.4 times higher than pristine PbO2 (0.0043 min −1 ). The biodegradability index (BOD/COD ratio) of pesticide wastewater after 180 min of treatment by CF/Bi-PbO2 and CF/PbO2 anodes was 0.62 and 0.29, respectively, which shows that the wastewater treated with Bi-doped anode is completely biodegradable. Graphical Abstract: ga1 Highlights: Anodically preparation of a 3D Bi-doped PbO2 anode on carbon felt substrate. Bi-doped anode has more OEP and service time compared to pristine PbO2 . Degradation of 97.6 % of diuron after 25 min of electrocatalytic degradation. Identifying the intermediates and suggesting diuron degradation pathways. Completely biodegradable pesticide wastewater after 180 min treatment.